The relationship between physical characteristics and match collision performance among elite international female rugby union players - Woodhouse, L. W.; Bennett, M.; Tallent, J.; Patterson, S. D.; Waldron, M. (European Journal of Sport Science, 2022)
This study investigated whether anthropometric and physical abilities explained variance in match collision performance among international female rugby union players. Physical performance and anthropometric data for fifty-one international female rugby union players, and collision actions categorised as "effort" or "performance" variables, from 20 international matches, were analysed using partial least squares regression. Among forwards, variance in carries/min was explained (R2 = .22) by a combination of; body mass, skinfolds, acceleration momentum and negative associations with mean aerobic speed and single-leg isometric squat relative force (SLISO/kgBM). Variance in collision dominance among forwards was explained (R2 = .21) by lower skinfolds and higher acceleration momentum, while tackles/min (R2 = .19) were explained by greater jumping power and single-leg isometric squat (SLISO). Among backs, variance in tackles/min (R2 = .54) was explained by greater bench press, SLISO and SLISO/kgBM. Variance in collision dominance among backs was explained (R2 = .23) by negative and positive associations with body mass and SLISO/kgBM, respectively. These findings suggest the development of physical characteristics, such as body mass and composition, strength and power contribute towards successful collision actions among international female rugby union players. The contribution of different physical characteristics towards collision events is dependent on position, and whether the collision event is categorised by "performance" or "effort". It is suggested that physical training programmes should reflect this level of specificity.